Georgia Architectural and Historic Properties Survey of Rural [117] Mid west section of the county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [117] Mid west section of the county, Quitman, Ga. December 1980. A one story rectangular plan with gabled tin roof and unpainted clapboard siding. Shed porch with square posts. Sash windows with 6/6 lights. Exterior chimney. Brick piers. Fair condition. Date of Construction: c. 1905. A typical vernacular farmhouse common to these rural areas.
Georgia Architectural and Historic Properties Survey of Rural [117] Mid west section of the county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 897 KB (918,549 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Brooks County (Ga.); Quitman (Ga.)